Faktor-faktor yang mempengaruhi perilaku konsumen dan organisasi - suswandi, feri _ (Maliki Interdisciplinary Journal, 2025)
This study aims to identify and analyze various factors that influence consumer behavior and the decisions made by organizations. Consumer behavior and the choices made by organizations are influenced by a number of both internal and external factors. Internal factors, such as individual psychology, motivation, attitudes, and social influences, play a significant role in shaping consumer preferences and behavior. On the other hand, external factors, including economic, cultural, technological aspects, and market changes, also have a significant impact on the strategies implemented by organizations to meet consumer needs and desires. Furthermore, the interaction between these factors also affects the dynamic relationship between consumers and organizations. By understanding the various factors influencing both parties, organizations can develop more efficient and responsive marketing strategies to adapt to changes in market needs.